2019
DOI: 10.1186/s43088-019-0010-3
|View full text |Cite
|
Sign up to set email alerts
|

Green production of silver nanoparticles, evaluation of their nematicidal activity against Meloidogyne javanica and their impact on growth of faba bean

Abstract: Background: Cyanobacterium-based silver nanoparticles are considered not only as an efficient nano-nematicide but also as a bio-stimulant material for plant growth. They could be employed as a part of an integrated program for controlling some plant diseases. Results: In this study, silver nanoparticles (Ag-NPs) were biosynthesized from aqueous extract of the cyanobacterium, Nostoc sp. PCC7524. Full characterization of the biosynthesized Ag-NPs was monitored by UV-vis spectroscopy, transmission electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…The adverse effect encountered might be due to the toxicity of green synthesized Ag@Cf L-NPs that inhibited the hatching of M. incognita. Similarly, increasing doses of Ag-NPs reduced the egg hatching of M. javanica as previously reported by Hamed et al (2019). The inhibition effect of Ag-NPs was correlated with the physical properties (size, shape, and homogeneity), which may play a crucial role in the cell wall penetration in the eggs followed by dysfunctioning in cells (Jagtap and Bapat, 2013).…”
Section: Effects Of Ag@cfl-nps On Hatching and Mortality Of Root-knot...supporting
confidence: 79%
“…The adverse effect encountered might be due to the toxicity of green synthesized Ag@Cf L-NPs that inhibited the hatching of M. incognita. Similarly, increasing doses of Ag-NPs reduced the egg hatching of M. javanica as previously reported by Hamed et al (2019). The inhibition effect of Ag-NPs was correlated with the physical properties (size, shape, and homogeneity), which may play a crucial role in the cell wall penetration in the eggs followed by dysfunctioning in cells (Jagtap and Bapat, 2013).…”
Section: Effects Of Ag@cfl-nps On Hatching and Mortality Of Root-knot...supporting
confidence: 79%
“…The analysis through FESEM-EDX spectrum recorded showing a sharp peak between 2.8 keV and 8.0 keV Fig. 8 confirmed the presence of an elemental silver signal of the silver nanoparticles [26].…”
Section: Energy-dispersive X-ray Spectrum Analysismentioning
confidence: 61%
“…This toxicity mechanism is also supported by Liang et al (2020) , who demonstrated that the high exposure concentration of mesoporous silica nanoparticles induced neurotoxicity in C. elegans nematodes. The toxicity of nanoparticles is not a species-specific ( Hamed et al 2019 ); hence, these findings on C. elegans may contribute to explain our results on M. incognita .…”
Section: Discussionmentioning
confidence: 65%